Rinodina evae (Physciaceae, Ascomycota), a new corticolous blastidiate species from Eastern Spain - Fos, Simón; Giralt, Mireia (Nova Hedwigia, 2009)
Rinodina evae, a new corticolous species, is described from Eastern Spain. It is mainly characterized by a blastidiate, hairy thallus, Pachysporaria-type ascospores and the lack of secondary lichen substances. Hitherto, it is only known from several cork-oak forests of Catalonia and the Valencian Community, where it always grows on virgin bark of Quercus suber. The new species is compared with Rinodina poeltiana, somewhat similar in habit, as well as with other corticolous blastidiate Rinodina species.
Keywords: Biodiversity; cork-oak forests; iberian peninsula; lichens; Rinodina; taxonomy

Rinodina evae (Physciaceae, Ascomycota), a new corticolous blastidiate species from Eastern Spain (Nova Hedwigia, 2009)
Rinodina evae, a new corticolous species, is described from Eastern Spain. It is mainly characterized by a blastidiate, hairy thallus, Pachysporaria-type ascospores and the lack of secondary lichen substances. Hitherto, it is only known from several cork-oak forests of Catalonia and the Valencian Community, where it always grows on virgin bark of Quercus suber. The new species is compared with Rinodina poeltiana, somewhat similar in habit, as well as with other corticolous blastidiate Rinodina species.

The Lichen Genus Usnea On Quercus Suber In Iberian Cork-Oak Forests (The Lichenologist, 2000)
Fifteen species of Usnea are recorded from Iberian cork-oak forests: U. ceratina, U. cornuta, U. dasaea, U. esperantiana, U. ﬂammea, U. fulvoreagens, U. glabrata, U. hirta, U. mutabilis, U. rubicunda, U. subcornuta, U. subﬂoridana, U. subscabrosa, U. substerilis and U. wasmuthii. A key for these species is provided. Details of morphology, chemistry, distribution, ecology and taxonomy are discussed. Usnea dasaea is reported as new to the Iberian Peninsula. New chemotypes of U. fulvoreagens (with squamatic acid) and U. wasmuthii (with psoromic acid) have been identiﬁed. Distribution maps of U. dasaea and U. subcornuta in Europe are presented. A new combination, Usnea subﬂoridana subsp. praetervisa (Asahina) P. Clerc, is proposed